Profit Cedera Akibat Jatuh, Kecelakaan Lalu Lintas dan Terluka Benda Tajam/Tumpul pada Masyarakat Indonesia - Riyadina, Woro (Jurnal Biotek Medisiana Indonesia, 2009)
Injury contributed to 15% mortality, 25% of disease burden and economic losses 5% GDP (Growth Product Development). Injury from traffic accidents, falls and injured by sharp/blunt object proportion occupied most of the causes of injury in the community, especially in developing countries. Advance analysis aims to compare the profile of injury from falls, traffic accidents and injured by sharp/blunt object on the people of Indonesia. This article is a public health data analysis resulted from 2007 basic health survey interview (Riskesdas) to 928,317 respondents from 33 provinces in Indonesia. The dependent variables were injury from falls, traffic accidents and injured by sharp/blunt object. Independent variables included the body part affected by injury, type of injury and the characteristics of the respondents (gender and type of urban or rural). Analysis of data using complex samples and weighted. Data are analyzed using the Chi square test to different proportions. Results indicated that the most of injury proportion in Indonesia were falls 59.5% (95% CI 58.9 -60.2), traffic accidents (land, sea and air) 27% (95% CI 26.4- 27.5) and injured by sharp/blunt object 18.3% (95% CI 17.7 - 18.9). The majority of the body part affected by injury was the extremities (hand and foot). Type of injury to falls and traffic accidents were supeificial, respectively 54.1% (95% CI 53.2- 54.9) and 65.9% (95% CI 64,9-66,8), meanwhile injured by sharp/blunt object was open wound 63.2% (95% CI 61.9 - 64.6). Order the highest proportion of fracture/amputation were traffic accidents (9.1%), falls (4.6%) and injured by sharp/blunt object (2.3%). As a conclusion that the profile of injury from falls, traffic accidents and injured by sharp/blunt object were different their characteristics. Traffic accident had the highest  severity  of injury (fracture/amputation) so its control needs to get priority.   Keywords: injuries, falls, traffic accidents, injured by sharp/blunt object